2012
DOI: 10.1371/journal.pone.0049970
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Fibroblast Growth Factor Receptors (FGFR) 1, 2 and 3 in the Regulation of S115 Breast Cancer Cell Growth

Abstract: Fibroblast growth factors (FGFs) regulate the growth and progression of breast cancer. FGF signaling is transduced through FGF receptors 1–4, which have oncogenic or anti-oncogenic roles depending on the ligand and the cellular context. Our aim was to clarify the roles of FGFR1–3 in breast cancer cell growth in vitro and in vivo. Pools of S115 mouse breast cancer cells expressing shRNA against FGFR1, 2 and 3 were created by lentiviral gene transfer, resulting in cells with downregulated expression of FGFR1, FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Interestingly, upregulation of the mRNA for Fgfr1c and downregulation of the mRNA for Fgfr2c were found in the prostates of FGF8b-Tg and FGF8b-Tg-BERKO FVB mice. This observation is consistent with our previous results in S115 mouse mammary tumor cells, MCF7 breast cancer cells (Ruohola et al 1995, Tarkkonen et al 2012, and the epididymides of FGF8b-Tg mice (Elo et al 2012), indicating that FGF signaling regulates the expression of FGFRs. Results described in a previous report have demonstrated that FGF8 upregulates the expression of Fgfr1 in the neuronal cells (Mott et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, upregulation of the mRNA for Fgfr1c and downregulation of the mRNA for Fgfr2c were found in the prostates of FGF8b-Tg and FGF8b-Tg-BERKO FVB mice. This observation is consistent with our previous results in S115 mouse mammary tumor cells, MCF7 breast cancer cells (Ruohola et al 1995, Tarkkonen et al 2012, and the epididymides of FGF8b-Tg mice (Elo et al 2012), indicating that FGF signaling regulates the expression of FGFRs. Results described in a previous report have demonstrated that FGF8 upregulates the expression of Fgfr1 in the neuronal cells (Mott et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Genomewide association studies have highlighted the role of single nucleotide polymorphisms in non-hereditary breast cancer susceptibility (Marian et al, 2011). As a result, fibroblast growth factor receptor 2 (FGFR2), a gene involved in mammary gland development, has been recognized as a prominent candidate in sporadic breast cancer (Sun et al, 2010;Tarkkonen et al, 2012). FGFR2 codes a transmembrane-type receptor involved in cellular functions .…”
Section: Introductionmentioning
confidence: 99%
“…Although, activating mutation and overexpression of FGFR3 is a common phenomenon observed in low-grade bladder cancer [19] , a switch from its epithelial to mesenchymal isoform with wider ligand affinity is thought to have more deleterious effects [19,26] . Particularly, Q2: Please confirm the running head FGFR1 has been considered as a potential oncogene in breast cancer because its deregulated signaling contributes to cell proliferation, growth, angiogenesis, EMT, and cell migration in S115 breast cancer [20] . Overall, FGFRs stands as an attractive target for therapeutic intervention in cancer [19,21,27] .…”
Section: Fibroblast Growth Factor Receptor (Fgfr) Familymentioning
confidence: 99%